Drug screening on digital microfluidics for cancer precision medicine - Zhai, Jiao; Liu, Yingying; Ji, Weiqing; Huang, Xinru; Wang, Ping; Li, Yunyi; Li, Haoran; Wong, Ada Hang-Heng; Zhou, Xiong; Chen, Ping; Wang, Lianhong; Yang, Ning; et al. (Nature communications, 2024)
Drug screening based on in-vitro primary tumor cell culture has demonstrated potential in personalized cancer diagnosis. However, the limited number of tumor cells, especially from patients with early stage cancer, has hindered the widespread application of this technique. Hence, we developed a digital microfluidic system for drug screening using primary tumor cells and established a working protocol for precision medicine. Smart control logic was developed to increase the throughput of the system and decrease its footprint to parallelly screen three drugs on a 4 × 4 cm 2 chip in a device measuring 23 × 16 × 3.5 cm 3 . We validated this method in an MDA-MB-231 breast cancer xenograft mouse model and liver cancer specimens from patients, demonstrating tumor suppression in mice/patients treated with drugs that were screened to be effective on individual primary tumor cells. Mice treated with drugs screened on-chip as ineffective exhibited similar results to those in the control groups. The effective drug identified through on-chip screening demonstrated consistency with the absence of mutations in their related genes determined via exome sequencing of individual tumors, further validating this protocol. Therefore, this technique and system may promote advances in precision medicine for cancer treatment and, eventually, for any disease. In-vitro platforms for personalized cancer diagnosis is required high sensitivity. Here, the authors developed a digital microfluidic system for drug screening using primary tumor cells and established a working protocol for precision medicine.